Rational design 3D nitrogen doped graphene supported spatial crosslinked Co3O4@NiCo2O4 on nickel foam for binder-free supercapacitor electrodes. (10th November 2018) - Wang, Ying; Zhang, Mingmei; Li, Yuan; Ma, Tianjiao; Liu, Hong; Pan, Denghui; Wang, Xinyu; Wang, An
Abstract: A three-dimensional spatial crosslinked Co3 O4 @NiCo2 O4 /N doped graphene (NG) growing on nickel foam has been prepared via hydrothermal reaction combining calcination. NiCo2 O4 with hollow tubular structure is not only beneficial to storage Co3 O4 nanoparticles, but also effectively maintains the neighboring NG nanosheets separated. With the help of this unique structure, the hybrid provides rich exposed electrochemical active sites and short-distance electron transport pathways. When directly serving as an electrode without using the binder for supercapacitors, Co3 O4 @NiCo2 O4 /NG/NF hybrid exhibits predominant specific capacitance (1094 C g −1 /2430 F g −1 at 1 A g −1 ), significant rate capability and persistent cycle life (retention of 93.7% even after 5000 continuous charge/discharge cycles) compared with other general electrode materials. The prepared asymmetric device provides a specific capacitance of 118.6 F g −1 at a current density of 1 A g −1, with a maximum energy density of 52.9 Wh kg −1 (power density of 544 W kg −1 ). The device still has an energy density of up to 23.9 Wh kg −1 at a maximum power density of 3630 W kg −1 .